Medyâtekst âk katalìzatar mounyh tendèncyj ì zakanamernascej - Vìktar Ì. (Stylistyka, 2019)
The article investigates the functioning of the Belarusian language in Belarus media, defines the role of language in the formation of a media trend in the situation of bilingualism, and shows the effect of information technology on journalism.